'Lower-income college student adjustments to COVID-19'. Issue 2 (19th January 2022) - Beck, Kristine; Chiu, Hsin-Hui; Timmerman, Inga
ABSTRACT: Using a survey of mostly low-income upperclassmen at a large public institution, we focus on the perspective of young adults regarding financial decision-making during the COVID-19 pandemic. We find that lower-income college students are weathering the pandemic by decreasing discretionary spending and increasing savings. In addition, we find most upperclassmen intend to finish their academic degree in the online learning environment.